Estimating Consumption Economies of Scale, Adult Equivalence Scales, and Household Bargaining Power - Browning, M.; Chiappori, P.-A.; Lewbel, A. (Review of Economic Studies, 2013)
How much income would a woman living alone require to attain the same standard of living that she would have if she were married? What percentage of a married couple's expenditures are controlled by the husband? How much money does a couple save on consumption goods by living together versus living apart? We propose and estimate a collective model of household behaviour that permits identification and estimation of concepts such as these. We model households in terms of the utility functions of its members, a bargaining or social welfare function, and a consumption technology function. We demonstrate generic non-parametric identification of the model, and hence of a version of adult equivalence scales that we call "indifference scales", as well as consumption economies of scale, the household's resource sharing rule or members' bargaining power, and other related concepts. Copyright 2013, Oxford University Press.